THE EFFECT OF DEMOCRATIC LEADERSHIP STYLE IN IMPROVING THE QUALITY HIGHER EDUCATION OF PGRI - BASED MANAGEMENT IN EAST JAVA - Abd Syakur; Sabar Narimo; Harun Joko Prayitno (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The goal of this study was to determine the effect of democratic leadership on the quality of processing higher education institutions (PT) on PGRI-based in East Java. This study employed a correlational quantitative research approach. The population of this study included all leaders of Private Higher Education (PTS) in the LLDIKTI VII East Java area, with a total of 60 samples chosen at random. With a 95 percent confidence level, the maximum error rate considered in this study was 5%. Based on the SPSS 26 test results, it was known that the instrument of democratic leadership style (X) and improving the quality of PT management (Y) was declared 'valid' with a calculated r value (X) of 0.758 and (Y) of 0.798 (with a r table value of 0.308). Cronbach Alpha values of 0.811 (X) and 0.856 (Y) indicated high reliability. The results of hypothesis testing (I) obtained the regression equation, namely Y = -2.765 + 0.225X, and the results of hypothesis testing (2) obtained t arithmetic (1.341) > t table (1.256) and a significance value of 0.02 > 0.05, so it can be concluded that Ha is accepted, which means that the democratic leadership style variable has a significant influence (there is still a low category influence relationship) on the quality of management of PGRI-based universities in East Java.